PENGARUH ASAL UMBI DAN PEMBERIAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascolonicum L.)VARIETAS LEMBAH PALU - Mule, Bahruddin, Yohanes Tambing, Yuliani (AGROTEKBIS, 2015)
The purpose of this study was to determine the effect of origin tuber and liquid organic fertilizer on growth and yield of onion lembah Palu varieties. This research was conducted by using a randomized block design 2 factors. The first factor is the treatment of seed from various places namely: A1 = Guntarano Village, A2 = Maku Village, A3 = Duyu Village, A4 = Bulu Pountu Jaya Village and A5 = Solouve Village. Factors to 2 that the treatment of liquid organic fertilizer DI Grow consists of two levels ie: B0 and B1 = = Control Organic Liquid Fertilizer. The results showed that the interaction between the origin of the tuber and liquid organic fertilizer at 40 HST observations of plant height and diameter of the leaf age of 40 and 50 HST. It was obtained higher plants and leaf area was greater in the liquid organic fertilizer on tuber origin Soulove village. The village tuber origin Guntarano provide more number of leaves and tubers larger diameter than the other bulbs origin. Liquid organic fertilizer and tuber origin has no effect on onion crop yield components in the form of fresh weight, wet weight, diameter and number of bulbs and tubers.